The A ZigBee protocol-based Security and alarm monitoring system at nursing homes - C. Rathiga,Edna Sweenie J,Prof.K. Prasanna ,Anusha,V. Sujatha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A ZigBee-based security monitoring and alarm system was presented in this study to reduce nursing home staff responsibilities. This method can keep tabs on five different aspects of an old person's health, including their urine in bed, their ambulation, their falling, their posture, and any bathroom accidents. First, the system's overall structure was explained, and then each function module was examined in further depth. For testing purposes, Beijing's Sijiqing elderly home put a monitoring system to the test and found it to be effective.